The Impact of Frailty on Adverse Outcomes in Geriatric Hip Fracture Patients: A Systematic Review and Meta-Analysis - Song, Yanhong; Wu, Ziyi; Huo, Huihui; Zhao, Ping (Frontiers in Public Health, 2022)
Objective: With an aging population and advances in medicine, more research focuses on health and longevity in geriatric adults. Recently, frailty has gradually emerged to assess physical conditions. Frailty can be generally described as a multi-dimensional situation of increased vulnerabilities to both endogenous and exogenous stressors. The objective of the review was to evaluate the predictive value of frailty on adverse outcomes in geriatric hip fracture patients. Materials and methods: We searched PubMed, Embase, Web of Science, and the Cochrane library for relevant literature about the connection between frailty and poor outcomes in hip fracture elders. Results: 11 studies involving a total of 45979 participants were selected in our study. Our results indicated that frailty could significantly predict postoperative and in-patient complications (OR,1.46;95%CI,1.13-1.90; I2=77.4%). Frail elders had higher risk of inpatient mortality (OR,1.68;95%CI,1.26-2.25; I2=0.0%), 6-month mortality (OR,1.46;95%CI,1.25-1.72; I2=0.0%) and greater than or equal to 1-year mortality (OR,2.24;95%CI,1.66-3.04; I2=91.3%). Furthermore, the risk of prolonged hospital stays was 1.15 times more likely in frail patients (95%CI,1.03-1.28; I2=14.8%). Conclusion: Frailty can predict adverse outcomes effectively in geriatric hip fracture patients.